The ability of three climbing plant species to capture particulate matter and their physiological responses at different environmental sampling sites - Lyu, Xiaoqian; Chang, Lu; Lu, Zhengyan; Li, Junfeng (Frontiers in Environmental Science, 2023)
The adsorption of particulate matter (PM) by the leaves of urban plants can effectively reduce the PM concentration in the atmosphere. The use of climbing plants to abate PM is an important means of urban greening in China, which is rich in climbing plant species. In this study, three evergreen climbing plants were selected to quantify their ability to adsorb PM and determine their physiological responses to particulate pollution. There were four key results. (1) The adsorption capacity of the three evergreen climbers followed the order of Hedera nepalensis var > Ficus pumila Linn > Euonymus fortunei, and was significantly higher in an overpass environment than in a campus environment for all three species. (2) The seasonal characteristics of particulate adsorption by the three types of climbers in both the overpass and campus environments followed the order of winter > autumn > spring > summer. (3) The net photosynthetic rate of the three climbing plants was significantly affected by PM in a size dependent manner, with fine PM on the plant leaf surface and coarse PM in the leaf waxy layer being important factors affecting plant photosynthesis. (4) Particulate pollution led to changes in the activities of plant protective enzymes in plants, with increases in the superoxide dismutase (SOD) and peroxidase (POD) activity, and the malondialdehyde (MDA) and soluble protein contents. There were different trends in the soluble sugar content among the different plant species. In conclusion, F. pumila had a strong resistance to particulate pollutants, while H. nepalensis was considered suitable for planting in polluted areas where it could improve ambient air quality by adsorbing large amounts of PM.